2019
DOI: 10.1161/circulationaha.118.035905
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Levels of Circulating Cytokines and Risk of Stroke

Abstract: Background: Cytokines and growth factors have been implicated in the initiation and propagation of vascular disease. Observational studies have shown associations of their circulating levels with stroke. Our objective was to explore whether circulating levels of cytokines and growth factors are causally associated with stroke and its etiologic subtypes by conducting a two-sample Mendelian randomization (MR) study. Methods: Genetic instruments for 41 cytokines and growth factors were obtained from a genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 190 publications
(197 citation statements)
references
References 50 publications
11
184
2
Order By: Relevance
“…Inflammatory biomarkers in blood, such as interleukin-6 and MCP-1, have been examined in AF patients; however, the relation between plasma MCP-1 levels and AF remains controversial. Plasma MCP-1 levels in patients with lone AF were reported to be higher compared to those in control subjects [23]; however, a recent genetic analysis reported that genetic predisposition to higher MCP-1 levels was not associated with atrial fibrillation [24]. It is noteworthy that the degree of fibrosis in atrial myocardium was correlated with MCP-1 levels in epicardial adipose tissue dissected from left atrial appendages in patients with AF [25].…”
Section: Plos Onementioning
confidence: 98%
“…Inflammatory biomarkers in blood, such as interleukin-6 and MCP-1, have been examined in AF patients; however, the relation between plasma MCP-1 levels and AF remains controversial. Plasma MCP-1 levels in patients with lone AF were reported to be higher compared to those in control subjects [23]; however, a recent genetic analysis reported that genetic predisposition to higher MCP-1 levels was not associated with atrial fibrillation [24]. It is noteworthy that the degree of fibrosis in atrial myocardium was correlated with MCP-1 levels in epicardial adipose tissue dissected from left atrial appendages in patients with AF [25].…”
Section: Plos Onementioning
confidence: 98%
“…Also, there are few data on stroke and other cardiovascular outcomes beyond coronary artery disease. [9][10][11] Interleukin-6 (IL-6), a key regulator of the inflammatory cascade, acts by binding to either its membrane-bound or soluble receptor (IL-6R) and induces proinflammatory downstream effects including increases in the levels of C-reactive protein (CRP). 12,13 IL-6 has been implicated in the pathogenesis of multiple inflammatory diseases and inhibitors of IL-6R are used for the treatment of rheumatoid arthritis, 14 inflammatory bowel disease, 15 and other autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS), which have identified thousands of variants associated with complex traits, bring the wide usage of MR to a new climax 22,23 . Recently, a comprehensive MR analysis regarding genetically determined levels of circulating cytokines and risk of stroke gave us a good demonstration 24 . It was implemented leveraging the most comprehensive GWAS which evaluated 41 cytokines and growth factors in 8293 healthy subjects of Finnish ancestry 25 , and the largest GWAS meta-analysis on stroke and stroke subtypes to date (MEGASTROKE) 26 .…”
Section: Introductionmentioning
confidence: 99%